A qualitative perception of Muslim women from the understanding of nonMuslims regarding Muslim women’s engagement in employment: a study based in the Ampara district, Sri Lanka - Mohamed Sulthan Ismiya Begum,; Indriaty Ismail,; Zul’azmi Yaakob, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article explores Muslim women's perceptions of non-Muslim understanding regarding their employment. The study, qualitative in nature, involved fourteen professional women from diverse academic and non-academic backgrounds, working in the public sector. These participants represented various locations in the Ampara district, including Sainthamaruthu, Maruthamunai, Ninthavur, Akkaraippatru, Sammanthurai, and Oluvil. Purposeful sampling was used to select the participants. Both primary and secondary sources were utilized for data collection. Semi-structured in-depth interviews were conducted, and the data was analyzed using Nvivo 10 software. Interviews were carried out in the participants' native language, Tamil, and were recorded, transcribed verbatim, and translated into English for analysis. The study found that non-Muslims hold diverse opinions about Islamic women's work. Muslim women strive to adhere to Islamic norms in various contexts, considering their femininity. The study suggests that Islam does not restrict their rights; rather, their perception is influenced by various sociocultural factors. By highlighting Muslim practices, non-Muslims gain a better understanding of Muslims, and Muslim women can clarify the teachings of Islam regarding their employment.